Acute hepatic porphyrias for the neurologist: current concepts and perspectives - Souza, Paulo Victor Sgobbi de; Badia, Bruno de Mattos Lombardi; Farias, Igor Braga; Gonçalves, Eduardo Augusto; Pinto, Wladimir Bocca Vieira de Rezende; Oliveira, Acary Souza Bulle (Arquivos de Neuro-Psiquiatria, 2021)
Background: Acute hepatic porphyrias represent an expanding group of complex inherited metabolic disorders due to inborn errors of metabolism involving heme biosynthesis. Objective: We aimed to review the main clinical and therapeutic aspects associated with acute hepatic porphyrias. Methods: The authors provided a wide non-systematic review of current concepts and recently acquired knowledge about acute hepatic porphyrias. Results: Acute neurovisceral attacks are the most common and life-threatening presentation of this group and are often considered the main clinical manifestation by clinicians during differential diagnosis and the start of proper diagnostic work-up for acute porphyrias. However, atypical presentations with central nervous system involvement, neuropsychiatric disturbances, and some subtypes with photosensitivity usually make the definite diagnosis difficult and late. Early therapeutic interventions are essential during emergency treatment and intercritical periods to avoid recurrent severe presentations. The availability of new disease-modifying therapeutic proposals based on small interfering RNA (siRNA)-based therapies, complementary to the classic intravenous glucose infusion and hemin-based treatments, emphasizes the importance of early diagnosis and genetic counseling of patients. Conclusions: This review article highlights the main biochemical, pathophysiological, clinical, and therapeutic aspects of acute hepatic porphyrias in clinical practice.
Keywords: Neuromuscular Diseases; Porphyria; Inborn Errors of Metabolism; Acute Intermittent Porphyria; Hepatic Porphyrias